Density functional estimation of hydride and proton affinities of substituted allenes and heteroallenes. (24th May 2021) - Saeidian, Hamid; Malekian, Hadi; Vessally, Esmail
Abstract: The hydride affinity (HA) of 20 allene and heteroallene derivatives containing unsaturated rings such as cyclopentadiene (CP) ring has been computationally investigated using the B3LYP/6‐311++G(3df, 2p) method. The interaction of hydride ion (H − ) with the central sp 1 carbon of the designed molecules containing electron‐withdrawing groups on the CP ring has been highly desirable, and their HA values were obtained in the range of 369–788 kJ/mol. The aromaticity of CP anion has the key role in the HA increasing and its stability. The harmonic oscillator model of aromaticity (HOMA) and nucleus‐independent chemical shifts (NICS) values associated with the CP ring were calculated and compared before and after the interaction with H − . The calculated data indicated a sharp increase in HOMA and NICS indices for the anions. In the following, the protonation of three designated allenes containing a cyclopropene or cycloheptatriene and a CP ring was also investigated using the density functional theory calculations. Electrostatic potential maps for some key structures were also used for charge distribution analysis. Abstract : The hydride affinity (HA) of the allene derivatives containing unsaturated rings such as cyclopentadiene (CP) ring has been investigated using B3LYP/6‐311++G(3df, 2p) method. Interaction of H − with central carbon of the molecules has been highly desirable, and their HA values were obtained in the range of 369–788 kJ/mol. The aromaticity of CP has the key role in the HA increasing. The data indicated a sharp increase in aromatic indices for the anions. Molecular electrostatic potentials (MEPs) were also used for charge distribution analysis.